Effect of Simultaneous Use of Different Amounts of Biochar and Soil Application of Common Sulfur and Spraying of Nanosulfur on Yield and Yield Components and Some Phytochemical Characteristics of Savory (Satureja hortensis L.) - Vahid Mohammadzadeh Kakhki; mohmmad Hossein Aminifard; Mohamad Behzad Amiri (بوم شناسی کشاورزی)
Introduction Savory (Satureja hortensis L.) is an annual aromatic medicinal plantbelonging to the Lamiaceae family. Its essential oil is used widely in medicine, food, health industries, and therapeutic processes. Additionally, the essential oil is an important part of traditional medicine to treat muscle pains, indigestion and diarrhea and infection diseases. Also, the relatively high vitamin C and vitamin A content of savory may contribute to long-term health by boosting the natural state of the human immune system. Biochar is a solid material formed by high-temperature charring of biomass under anaerobic conditions. It has a large specific surface area, high porosity, and abundant nutrients, such as nitrogen, potassium, and calcium. As a result of these properties,  applying biochar as an organic soil amendment has been considered as an option to improve agricultural systems. The great potential of biochar application has also been directly reflected in plant growth and crop productivity. Biochar can potentially remediate salt-affected soils through salt sorption. Specifically, biochar sorption of Na+ in the soil solution can both reduce plant Na uptake and increase the relative uptake of Ca2+ and Mg2+. More broadly, biochar can generally enhance plant growth by improving soil properties, such as cation-exchange capacity (CEC), water retention capacity, and bulk density. Biochar can reduce fertilizer and water use by increasing the soil CEC and water-holding capacity (WHC).Using sulfur (especially in soil with low sulfur content) improves soil properties and increases plant growth and yield. The biochemical oxidation of elemental sulfur produces sulfuric acid (H2SO4), which decreases soil pH and solubilizes CaCO3 in alkaline soils to make soil conditions more favorable for plant growth. Sulfur is a part of an enzyme necessary for nitrogen absorption. Its deficiency can significantly hinder nitrogen metabolism, as sulfur and nitrogen are required to form amino acids essential for protein synthesis. Sulfur is also present in fatty acids and vitamins, playing a key role in crops' quality, taste, and aroma. Nano-fertilization is an agricultural technique that enhances crop growth, improves nutrient efficiency, and reduces fertilizer waste and costs. It promotes better crop development by providing more surface area for various metabolic reactions, thereby increasing the rate of photosynthesis and overall crop productivity while preventing biotic and abiotic stress. Material and Methods To evaluate the combined application of ecological inputs, specifically biochar and sulfur nutritional treatments, on the medicinal plant savory (Satureja hortensis L.), a split-plot experiment based on a randomized complete block design (RCBD) with three replications was conducted over the 2020-2021 and 2021-2022 growing seasons at the Research Field of the University of Gonabad, Iran. The data were analyzed using composite analysis. Different biochar levels (5, 10, and 20 t.ha⁻¹, plus a control) and sulfur nutritional treatments (common sulfur, nano-sulfur, and control) were assigned to the main and subplots, respectively.Results and Discussion The results of this study showed that the highest and lowest seed number per m2 and flowering shoot weight were obtained in treatments of 20 t.ha-1 biochar and spraying of nanosulfur (with 27777 seeds per m2 and 25.67 g flowering shoot, respectively) and non-application of biochar and control (with 8024 seeds per m2 and 6.24 g flowering shoot, respectively). The results of triple interaction effects of different amounts of biochar, nutritional treatments, and cropping year showed that the highest seed yield (10.74 g.m2) and biological yield (46.91 g.m2) were observed in the first cropping year and treatments of simultaneous application of 20 t.ha-1 biochar and spraying of nanosulfur. The interaction effects of biochar and nutritional treatments showed that the highest oil was obtained in the treatment of 10 t.ha-1 biochar and soil application of common sulfur. The total phenol, flavonoid content, and antioxidant activity decreased with the simultaneous application of biochar and sulfur nutritional treatments. The highest levels of these traits were observed when no biochar was applied in combination with the nutritional treatments.Conclusion In general, according to the findings of this research, the simultaneous application of high amounts of biochar (levels of 10 and 20 t.ha-1) and sulfur nutritional treatments, especially spraying of nano-sulfur, led to improved yield and yield components, but the qualitative characteristics of savory were reduced due to the combined use of these ecological inputs.AcknowledgmentsThis research was financially supported by the University of Birjand, Iran.